REVIEW OF ISLAMIC LAW AND CUSTOMARY LAW ON THE MODEL OF THE DIVISION OF INHERITANCE IN THE BETAWI AND MINANGKABAU TRIBES, A COMPARISON - Al-hakim, Shidiq; Unang Fauzi; Hendri Tanjung; Rizky Siswanto (al-Mawarid Jurnal Syariah dan Hukum (JSYH), 2024)
This research investigates two crucial aspects of Indonesian culture, namely the inheritance division traditions in the Betawi and Minangkabau tribes, and how these traditions interact with the Islamic worldview. The research uses a qualitative approach, descriptive methods, and legal, sociological, and philosophical analyses to understand how the inheritance division traditions in these societies reflect the influence of the Islamic Worldview. The results show that both tribes retain elements of their distinctive culture in the division of inheritance, although the influence of Islam is visible in a number of aspects. Although there are differences with Islamic teachings in some respects, the principles of equality and justice remain an integral part of this tradition. Given the complexity of interpreting and implementing religious values in diverse cultural contexts, this research provides a deep insight into the interaction between Islam, adat and inheritance division in Indonesia. The findings of this study provide a basis for further comparisons with other cultural and religious contexts as well as practical implications for strengthening the principles of justice in inheritance systems in these societies. Penelitian ini menginvestigasi dua aspek krusial dalam budaya Indonesia, yaitu tradisi pembagian warisan dalam suku Betawi dan suku Minangkabau, serta bagaimana tradisi-tradisi ini berinteraksi dengan pandangan dunia Islam. Penelitian menggunakan pendekatan kualitatif, metode deskriptif, dan analisis hukum, sosiologis, serta filosofis untuk memahami bagaimana tradisi pembagian warisan dalam masyarakat ini mencerminkan pengaruh Islamic Worldview. Hasil penelitian menunjukkan bahwa kedua suku tersebut mempertahankan unsur-unsur khas budaya mereka dalam pembagian warisan, meskipun pengaruh Islam terlihat dalam sejumlah aspek. Walaupun terdapat perbedaan dengan ajaran Islam dalam beberapa hal, prinsip-prinsip kesetaraan dan keadilan tetap menjadi bagian integral dari tradisi ini. Dengan kompleksitas penafsiran dan implementasi nilai-nilai agama dalam konteks budaya yang beragam, penelitian ini memberikan wawasan yang mendalam mengenai interaksi antara Islam, adat, dan pembagian warisan di Indonesia. Temuan penelitian ini memberikan dasar bagi perbandingan lebih lanjut dengan konteks budaya dan agama lainnya serta implikasi praktis untuk memperkuat prinsip-prinsip keadilan dalam sistem waris di masyarakat ini.